Mathematics Learning Children with Special Needs: Identification of Independence in the Mathematics Learning Process for Students with Learning Difficulties - Hermawan, Budi; Hufad, Achmad; Rochyadi, Endang; Sunardi, Sunardi; Maryanti, Rina; Fatimatuzzahra, Ana; Taboer, Mohamamd Arief (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to find out the profile of the independence of the mathematics learning process for children with special needs, especially students with learning difficulties. We used a qualitative research method with the subject of children with special needs (students with learning difficulties) in junior high schools, in West Java. The results showed that independence in the process of learning mathematics for students with learning difficulties can be analyzed from 3 aspects, namely: (1) independent learning in the aspect of freedom to make choices, (2) independent learning in the aspect of commitment to assignments, and (3) independent learning in aspects of self-confidence. This can be seen from the analysis of data taken from the field. Most children have a large percentage of their belief in the aspects of learning independence in the aspect of belief in their own abilities. The implications of this research are expected to be a reference in developing programs or determining learning methods used for students with learning difficulties.